LUM Expression and Its Prognostic Significance in Gastric Cancer - Chen, Xiaowei; Li, Xin; Hu, Xueju; Jiang, Fei; Shen, Yan; Xu, Rui; Wu, Leilei; Wei, Pingmin; Shen, Xiaobing (Frontiers in Oncology, 2020)
Background. Lumican (LUM) is a member of the small leucine-rich proteoglycan family, and plays dual roles as an oncogene and a tumor suppressor gene. The effect of LUM on tumors is still controversial. Methods. Gene expression profiles and clinical data of gastric cancer (GC) were downloaded from The Cancer Genome Atlas (TCGA) database. The expression difference of LUM in GC tissues and adjacent nontumor tissues was analyzed by R software, and verified by quantitative real-time polymerase chain reaction (qRT-PCR) and comprehensive meta-analysis. The relationship between LUM expression and clinicopathological parameters was assessed by chi-square test and logistic regression. Kaplan-Meier survival analysis and the Cox proportional hazards regression model were chosen to assess the effect of LUM expression on survival. Gene set enrichment analysis (GSEA) was used to screen signaling pathways involved in GC between the low and high LUM expression data sets. Results. The expression of LUM in GC tissues was significantly higher than that in adjacent nontumor tissues (P < 0.001) from the TCGA database. qRT-PCR (P = 0.022) and comprehensive meta-analysis (SMD = 0.90, 95% CI: 0.34-1.46) demonstrated that LUM was upregulated in GC. The chi-square test showed that the high expression of LUM was correlated with tumor differentiation (P = 0.024) and T stage (P = 0.004). Logistic regression analysis showed that high LUM expression was significantly correlated with tumor differentiation (OR=1.543 for poor vs. well or moderate, P=0.043), pathological stage (OR= 3.149 for Stage II vs. Stage I, P=0.001; OR=2.505 for Stage III vs. Stage I, P=0.007), and T classification (OR=13.304 for T2 vs. T1, P=0.014; OR=18.434 for T3 vs. T1, P=0.005; OR=30.649 for T4 vs. T1, P=0.001). Kaplan-Meier curves suggested that patients with high LUM expression had a poor prognosis. Multivariate analysis showed that high expression of LUM was an important independent predictor of poor overall survival (HR, 1.189; 95% CI, 1.011-1.400; P=0.037). GSEA indicated that fourteen signaling pathways were evidently enriched in samples with the high-LUM expression phenotype. Conclusions. LUM might act as an oncogene in the progression of GC and could be regarded as a potential prognostic indicator and therapeutic target for GC.